Pengaruh Senam Irama Terhadap Perkembangan Kecerdasan Kinestetik Anak Usia 5-6 Tahun di TK Alkhairat Kecamatan Kota Utara Kota Gorontalo - Delsi D. Gobel; Yenti Juniarti; Sulastya Ningsih (Institut Nalanda, 2024)
Delsi D. Gobel 2024 The Effect of Rhythmic Gymnastics on the Kinesthetic Intelligence of Children Aged 5-6 Years at Alkhairat Kindergarten, Kota Utara, Gorontalo. Department of Early Childhood Teacher Education, Faculty of Education, Universitas Negeri Gorontalo, The Principal Supervisor is Yenti Juniarti, S.Pd., M.Pd. and The Co-Supervisor is Sulastya Ningsih, S.Pd., M.Pd. This study aims to investigate rhythmic gymnastics' effect on kinesthetic intelligence development in children aged 5-6 years at Alkhairat Kindergarten in Kota Utara, Gorontalo. This study employs a quantitative experimental method utilizing a pre-test and post-test design, wherein tests are administered before and after the treatment. The study subjects consisted of 16 children aged 5-6 years from Group B at Alkhairat Kindergarten, Kota Utara, Gorontalo. The objective is to enhance the development of children's kinesthetic intelligence through rhythmic gymnastics. Data collection for the pre-test and post-test was conducted via observations using research instruments. The results indicate a significant difference in the average scores of kinesthetic intelligence before and after the treatment, evidenced by the pre-test and post-test scores of 15,31 and 30,81, respectively. These results demonstrate a considerable effect of the treatment. Based on the t-test calculations, the significance value (2-tailed) is 0.000 <0.05, leading to the rejection of HO and confirmation of H1. Thus, it can be concluded that rhythmic gymnastics significantly affects kinesthetic intelligence.